2021
DOI: 10.1002/mds.28610
|View full text |Cite
|
Sign up to set email alerts
|

Regional Brain and Spinal Cord Volume Loss in Spinocerebellar Ataxia Type 3

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
56
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 36 publications
6
56
0
Order By: Relevance
“…This may provide support for the concept that these regions show altered neuronal activity due to disconnection (or other downstream network effects) from cerebellum and striatum, two core structures that are directly affected by local pathology. Regarding structural disconnection, studies have also found evidence for affected (infratentorial) white matter structures, and an association with disease progression and ataxia severity ( Faber et al, 2021 , Rezende et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…This may provide support for the concept that these regions show altered neuronal activity due to disconnection (or other downstream network effects) from cerebellum and striatum, two core structures that are directly affected by local pathology. Regarding structural disconnection, studies have also found evidence for affected (infratentorial) white matter structures, and an association with disease progression and ataxia severity ( Faber et al, 2021 , Rezende et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Guo et al studied 47 SCA3 subjects in a Chinese population and showed progressive atrophy in cerebellar gray matter and several cerebrum regions ( 22 ). Faber et al gathered 210 SCA3 subjects from 8 countries (Brazil, China, France, Germany, Netherland, Spain, UK, and US) and found atrophy in cerebellum, brainstem, thalamus, basal ganglia with dilation of ventricle ( 23 ). Hernandez-Castillo et al studied 17 SCA3 patients from Mexican population and found atrophy in cerebellum, pons and left lingual gyrus ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent publications have reported variable findings in the volumetry of various anatomical brain structures in patients with SCA3 (17)(18)(19)(20)(21)(22)(23)(24). One recent study reported that patients with SCA 3 had decreased cerebellar and cerebral volumes, and also the basal ganglia, gray matter and the thalamus (18).…”
Section: Introductionmentioning
confidence: 99%
“…Aside from the common features mentioned above, SCA3 can be distinguished from other SCAs by the presence of pyramidal and extrapyramidal motor dysfunctions. Degeneration in SCA3 patient brains is often seen in the dentate neurons of the cerebellum, pontine nuclei, brainstem, and basal ganglia [103][104][105]. As with most SCA diseases, SCA3 also includes a number of non-motor symptoms-including sleep and mood disorders, depression, as well as cognitive and other psychiatric disturbances [106,107].…”
Section: Spinocerebellar Ataxia Type 3 (Sca3)mentioning
confidence: 99%